Block copolymer self-assembly assisted fabrication of laterally organized- and stacked- nanoarrays. (7th January 2022) - Suresh, Vignesh; Chew, Ah Bian; Tan, Christina Yuan Ling; Tan, Hui Ru
Abstract: Block copolymer (BCP) self-assembly processes are often seen as reliable techniques for advanced nanopatterning to achieve functional surfaces and create templates for nanofabrication. By taking advantage of the tunability in pitch, diameter and feature-to-feature separation of the self-assembled BCP features, complex, laterally organized- and stacked- multicomponent nanoarrays comprising of gold and polymer have been fabricated. The approaches not only demonstrate nanopatterning of up to two levels of hierarchy but also investigate how a variation in the feature-to-feature gap at the first hierarchy affects the self-assembly of polymer features at the second. Such BCP self-assembly enabled multicomponent nanoarray configurations are rarely achieved by other nanofabrication approaches and are particularly promising for pushing the boundaries of block copolymer lithography and in creating unique surface architectures and complex morphologies at the nanoscale.